Lewis Acid Promoted Trapping of Chiral Aza-enolates - Lanza, Francesco; Pérez, Juana M.; Jumde, Ravindra P.; Harutyunyan, Syuzanna R. (Synthesis, 2019)
We present a study on sequential conjugate addition of Grignard reagents to alkenyl-heteroarenes followed by trapping of the resulting enolates, yielding moderate to good diastereoselectivities. Contrary to conventional wisdom, one-pot conjugate addition/trapping using two reactive Michael acceptors in combination with Grignard reagents can proceed via conjugate addition to the least reactive Michael acceptor. This unusual chemoselectivity is triggered by the presence of a Lewis acid, reverting the usual reactivity order of Michael acceptors.
Keywords: aza-enolate trapping; copper catalyst; Lewis acid; conjugate addition; one-pot reaction